How do formative objective structured clinical examinations drive learning? Analysis of residents' perceptions. (2nd January 2018) - Pugh, Debra; Desjardins, Isabelle; Eva, Kevin
Abstract: Introduction: Although several studies have explored the relationship between learning and written tests, little is understood about how performance-based examinations influence learning. The purpose of this study was to explore how a formative objective structured clinical examination (OSCE) drives learning. Methods: We administered surveys to residents ( n  = 35) at three time points to determine if and how an OSCE influenced their learning: before and immediately following the OSCE, and after the distribution of their results. Differences in quantitative responses between high- and low-performing residents and across time were compared using repeated-measures ANOVA. Thematic analysis was used to analyze narrative comments. Results: Participants' goals for the OSCE related to performance, mastery and feedback. Almost all participants reported that they had learned something from the OSCE (94%) and most participants generated learning goals after the OSCE (71%). High performers appeared to recognize the importance of content-related knowledge for scoring well before and after the OSCE, whereas low performers may have under-estimated its importance until after the examination. Discussion: Participants viewed a formative OSCE as both a hurdle to overcome (assessment of learning) and an opportunity to learn (assessment for learning). Understanding how OSCEs influence study behavior can help guide the development of assessments that promote learning.